SYMBIOTIC NOVA V1016 CYG AS INTERACTING BINARY - Parimucha, S.; Chochol, D.; Pribulla, T. (Одеські астрономічні публікації, 2017)
Long-term UBV photoelectric and photographic photometry of the symbiotic nova V1016 Cyg is discussed. The pre-outburst brightening in 1949, main nova-like outburst in 1964 and two small brightenings in 1980 and 1994 suggest 15.1 ± 0.2 years period of activity. It is shown that a variation in the (J - K) colour index as well as that in the UV continuum and emission line in the IUE, HUT and HST spectra exhibit the same periodicity, which is interpreted as the orbital period of the binary on an eccentric orbit. The basic parameters of the system are given.